Prenatal nicotine exposure enhances the trigeminocardiac reflex via serotonin receptor facilitation in brainstem pathways - Gorini, C. (American Physiological Society, 2013)
In this study we used a rat model for prenatal nicotine exposure to test whether clinically relevant concentrations of brain nicotine and cotinine are passed from dams exposed to nicotine to her pups, whether this changes the trigeminocardiac reflex (TCR), and whether serotonergic function in the TCR brainstem circuitry is altered. Pregnant Sprague-Dawley dams were exposed to 6 mg·kg(−1)·day(−1) of nicotine via osmotic minipumps for the duration of pregnancy. Following birth dams and pups were killed, blood was collected, and brain nicotine and cotinine levels were measured. A separate group of prenatal nicotine-exposed pups was used for electrophysiological recordings. A horizontal brainstem slice was obtained by carefully preserving the trigeminal nerve with fluorescent identification of cardiac vagal neurons (CVNs) in the nucleus ambiguus. Stimulation of the trigeminal nerve evoked excitatory postsynaptic current in CVNs. Our data demonstrate that prenatal nicotine exposure significantly exaggerates both the TCR-evoked changes in heart rate in conscious unrestrained pups, and the excitatory neurotransmission to CVNs upon trigeminal afferent nerve stimulation within this brainstem reflex circuit. Application of the 5-HT(1A) receptor antagonist WAY 100635 (100 μM) and 5-HT(2A/C) receptor antagonist ketanserin (10 μM)significantly decreased neurotransmission, indicating an increased facilitation of 5-HT function in prenatal nicotine-exposed animals. Prenatal nicotine exposure enhances activation of 5-HT receptors and exaggerates the trigeminocardiac reflex.